Anthrax Seroprevalence in Central Java, Indonesia - Redhono, Dhani; Dirgahayu, Paramasari (Indonesian Journal of Medicine, 2016)
Background: Anthrax is a zoonotic disease that is caused by Bacillus Anthracis is transmitted to humans through infected animal. The transmission to humans occurs when there is a contact to animals or animal products contracting anthrax. Clinical skin manifestations and anthrax serum Ig G antibody can be used to diagnose infected anthrax animals. This study aimed to determine the prevalence of anthrax based on ELISA serum Ig G antibody and clinical skin manifestations occurring in patients with anthrax.Subjects and Method: This was a descriptive study with cross sectional design conducted in Sragen district, Central, Indonesia, in 2015. A sample of 101 patients infected with anthrax was examined based on clinical skin manifestations and anthrax serum Ig G antibody.Results: 39.6% of the sample was 21 to 40 years of age. 57.4% of the sample was female. 74% of the sample completed primary school. 21% worked as farmers. 30.5% of the sample who cooked and consumed meat showed positive Ig G. Test results showed serum Ig G antibody negative 50%, 15.8% and 33.7% borderline positive. Clinical manifestations in the skin as much as 11.9%, which is the eschar on all respondents and 92.8% showed positive IgÃÂ  G. While 88.1% did not show any clinical signs of anthrax.Conclusion: The increase in serum antibody titer Ig G anthrax is not all respondents were exposed, in an area that otherwise outbreak of anthrax, which is only a third of all respondents, and when it comes up eschar will be followed by an increase in Ig G antibody titer.Keywords: cutaneous anthrax, Ig G antibody ELISA, escharCorrespondence:ÃÂ Dhani Redhon. Sub Division Tropical Medicine and Infectious Disease, Internal Medicine.Indonesian Journal of Medicine (2016), 1(2): 129-135https://doi.org/10.26911/theijmed.2016.01.02.07